2022
DOI: 10.3389/fnut.2022.959039
|View full text |Cite
|
Sign up to set email alerts
|

Higher niacin intakes improve the lean meat rate of Ningxiang pigs by regulating lipid metabolism and gut microbiota

Abstract: As one of the local pig breeds in China with a high fat rate, improving the lean meat rate of Ningxiang pigs through nutritional intervention is an urgent issue to be solved. As an important feed additive, niacin plays an important role in lipid metabolism. The purpose of this study was to investigate the regulation and mechanism of niacin on fat deposition in Ningxiang pigs. Thirty-four Ningxiang pigs (53.34 ± 2.78 kg) were randomly divided into two groups with five replicates each, with three to four Ningxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…MG had significantly more Campilobacterota than MN, while the Firmicutes level was significantly lower, consistent with the findings of Mainz et al 31 , who observed similar changes in a mouse model of alcoholic liver disease. Wang et al 32 also found that Firmicutes and Actinobacteriota were associated with changes in adiposity and leanness in pigs, suggesting a possible link between liver fibrosis development and fat and alcohol-metabolizing microbiota in vivo. At the genus level, the dominant genera in the intestinal microbiota of MG and MN were Prevotella , Lactobacillus , Treponema , Rikenellaceae_RC9_gut_group , and Eubacterium_coprostanoligenes_group .…”
Section: Discussionmentioning
confidence: 96%
“…MG had significantly more Campilobacterota than MN, while the Firmicutes level was significantly lower, consistent with the findings of Mainz et al 31 , who observed similar changes in a mouse model of alcoholic liver disease. Wang et al 32 also found that Firmicutes and Actinobacteriota were associated with changes in adiposity and leanness in pigs, suggesting a possible link between liver fibrosis development and fat and alcohol-metabolizing microbiota in vivo. At the genus level, the dominant genera in the intestinal microbiota of MG and MN were Prevotella , Lactobacillus , Treponema , Rikenellaceae_RC9_gut_group , and Eubacterium_coprostanoligenes_group .…”
Section: Discussionmentioning
confidence: 96%
“…A 100 mg sample was accurately measured, ground, and added to the extraction solution at 4℃ for metabolite extraction, followed by centrifugation of the supernatant metabolite solvent for liquid mass spectrometry ( LC-MS ) detection. The procedures were the same as that described in the previous study ( Wang, et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%